Crafting with copper 25 creative projects for home & garden - Freiband, Jana 1952- (Chanhassen, MN Creative Pub, 2007)
"Introduces readers to creative metal work and gives complete plans and directions for 25 easy-to-build projects for the home and garden"--Provided by publisher
Includes index
Keywords: Copperwork